Answer:
see explanation
Step-by-step explanation:
Using the trigonometric identities
• cscA = [tex]\frac{1}{sinA}[/tex]
• secA = [tex]\frac{1}{cosA}[/tex]
• tanA = [tex]\frac{sinA}{cosA}[/tex]
• sin²A + cos²A = 1
(1)
consider the left side
cscA tanA
= [tex]\frac{1}{sinA}[/tex] × [tex]\frac{sinA}{cosA}[/tex] ( cancel sinA )
= [tex]\frac{1}{cosA}[/tex]
= secA
= right side ⇒ proven
(2)
consider the left side
[tex]\frac{sinA}{cscA}[/tex] + [tex]\frac{cosA}{secA}[/tex]
= [tex]\frac{sinA}{\frac{1}{sinA} }[/tex] + [tex]\frac{cosA}{\frac{1}{cosA} }[/tex]
= sinA × sinA + cosA × cosA
= sin²A + cos²A
= 1
= right side ⇒ proven